Rapid change in plankton community structure during spring along the eastern Beagle Channel - Cadaillón, Andreana Mackenna (2023)
In November 2019, a first joint Chilean–Argentinian research cruise was conducted along the eastern section of the Beagle Channel (BC). Here we present the results of the microbial plankton (2–200 μm cell size) abundance and composition analyses in relation to water masses and environmental variables, along a longitudinal transect characterized by contrasting hydrology. Plankton samples were analyzed within the photic zone along the channel and at two fixed stations during two short time series (a first one of 30 and a second one of 42 h). Results revealed a spatial zonation in the composition and structure of the plankton assemblages, related to bathymetry, water temperature and nutrient availability but also, a small-scale temporal variability due mainly to a rise in air and water temperature. The inner (westernmost) and outer sectors of the sampled area, west and east of Mackinlay Strait, respectively, were characterized by low plankton abundances, mostly dominated by nanoflagellates and some large diatoms. In contrast, the easternmost sector of BC, showed the highest total cell abundances, displaying a high diversity of small and large diatoms. Notably, in the inner BC (fixed station F1), chl-a concentrations almost doubled in 24 h, along with an increase in total plankton abundance and the dominance of small diatoms and nanoflagellates. Rapid changes in plankton relative abundance were also observed east to Mackinlay Strait. This highlights the large spatial (km) and temporal (hours to days) plankton heterogeneity along the eastern section of the BC, scales which should be considered for further sampling strategies.